On a moment estimate of sum of weakly dependent random variables using simple random walk on graph - Spektor , Susanna (North-Western European Journal of Mathematics, 2020)
We obtained a moment estimate for the sum of Rademacher random variables under condition that they are dependent in the way that their sum is zero.